Dear China : Emigrant Letters and Remittances, 1820-1980 - Benton, Gregor; Liu, Hong, 1962- (Book collections on Project MUSE., 2018)
"Qiaopi is one of several names given to the 'silver letters' Chinese emigrants sent home in the nineteenth and twentieth centuries. These letters-cum-remittances document the changing history of the diaspora in different parts of the world and different periods, and its ties to China. The qiaopi trade played a big part in making China transnational. This book, the first in English on qiaopi and on the origins, structure, and operations of the qiaopi trade, makes an important contribution to our understanding of modern Chinese history and to the comparative study of global migration"--Provided by publisher.